Spiritual Education in the Islamic Studies Curriculum in West - Omara, Attia; Berghout, Abdelaziz (EIMJ, 2025)
The Islamic studies curriculum in the West is still in its early stages of development compared to the advancements in the number of Islamic centers, schools, teacher training programs, civic education initiatives, and efforts to contextualize Islam for multicultural societies. However, the integration of spiritual teachings of tazkiyah (self-purification) and taṣawwuf (Sufism), remains largely overlooked. This paper examines three prominent Islamic curricula in the United States—ICO, Safar, and Weekend Islamic Studies revealing a focus on rational knowledge while marginalizing spiritual teachings and experiential learning of the Divine. The study advocates for the need of tajdīd (renewal) as a solution, emphasizing the need to simplify and adapt Sufi and spiritual teachers for development of curriculum that nurtures maʿrifah (knowledge of God) and maḥabbah (Divine Love). Such integration can enrich students' moral and spiritual consciousness, enabling lives guided by faith (īmān), virtuous action (ʿamal ṣāliḥ), and certainty (yaqīn).